Artificial intelligence for predicting the risk of bone fragility fractures in osteoporosis - Fabio Massimo Ulivieri; Carmelo Messina; Francesco Maria Vitale; Luca Rinaudo; Enzo Grossi (European Radiology Experimental, 2025)
Abstract Osteoporosis is widespread with a high incidence rate, resulting in fragility fractures which are a major contributor to mortality among the elderly. Artificial intelligence (AI), in particular artificial neural networks, appears to be useful in managing osteoporosis complexity, where bone mineral density usually reduces with aging, losing the pivotal role in decision-making regarding fracture prediction and treatment choice. Nevertheless, only some osteoporotic patients develop fragility fractures, and treatments often are not prescribed because of the high costs and poor patient adherence. AI can help clinicians to identify patients prone to fragility fractures who can benefit from preventive interventions. We describe herein the methodology issues underlying the potential advantages of introducing AI methods to support clinical decision-making in osteoporosis, being aware of challenges regarding data availability and quality, model interpretability, integration into clinical workflows, and validation of predictive accuracy. The fact that no AI fracture risk prediction software is still publicly available can be related to the fact that few high-quality datasets are available and that AI models, particularly deep learning approaches, often act as ‘black boxes’, making it difficult to understand how predictions are made. In addition, the effective implementation of predictive software has not reached sufficient integration with existing systems. Relevance statement With aging, bone mineral density may lose the pivotal role in osteoporosis decision-making regarding fracture prediction and treatment choice. In this scenario, AI, particularly artificial neural networks (ANNs), can be useful in supporting the clinical management of patients affected by osteoporosis. Key Points Osteoporosis is a complex disease with many interlinked clinical and radiological variables. Bone mineral density and other known indices do not allow optimal decision-making in patients affected by osteoporosis. ANN analysis can better discriminate osteoporotic patients particularly prone to fragility fractures and can predict future fractures. Graphical Abstract